The Impact of Antenatal Care and Pre-Referral Emergency Management on Eclampsia-Related Maternal Mortality in a Low-Resource Setting - Baskoro, Boyong; Laksana, Muhammad Ardian Cahya; Prasetyo, Budi (South Eastern European Journal of Public Health, 2024)
Backgrounds: Maternal mortality due to eclampsia had a high case fatality rate. This is frequently due to a failure in detection and monitoring during the ANC, as well as inadequate emergency management of eclampsia. Objective: To determine the impact of ANC and pre-referral emergency management of eclampsia-related maternal death at Dr. Soetomo and Airlangga University Hospital, Surabaya, Indonesia Methods: Analytical study with a retrospective cohort design from 2022-2023, using medical records of eclampsia patients referred to Dr. Soetomo Hospital and Airlangga University Hospital to investigate the relationship between ANC, pre-referral emergency management of eclampsia-related maternal death. Bivariate analysis used the Chi-square test, while multivariate analysis used logistic regression. Results: A total of 59 out of 65 patients met the inclusion criteria. Statistical analysis showed that study subjects aged ≥ 35 years had an association with maternal mortality in eclampsia cases (p = 0.007). A significant relationship also occurred in subjects who were not screened for preeclampsia (p = 0.013) and subjects who did not receive inadequate management of eclampsia (p = 0.000). Conclusion: Pre-referral emergency management of eclampsia is associated with eclampsia-related maternal death, hence health facilities must increase their ability to address eclampsia emergencies before referral.